Substitution of Kiwi Extract and Egg White Extract in a Special Formula for Severe Hypoalbuminemia in Type 2 Diabetes Mellitus and Hypertension Patients - Ramadhani, Millennia Rillys; Sutjiati, Endang; Adelina, Rany (El-Hayah:Jurnal Biologi, 2024)
Diabetes Mellitus (DM) and Hypertension are global health emergencies as declared by the World Health Organization. Hypoalbuminemia, often associated with severe illnesses, disrupts physiological processes and hinders recovery. This study developed and evaluated a modified enteral formula for diabetic patients with complications using local ingredients, specifically kiwifruit juice and egg white extract, known to reduce blood pressure and enhance albumin levels. The study employed a true-experimental design with a Completely Randomized Design (CRD). Three formulations were created by varying the proportions of diabetic milk, kiwifruit juice, and egg white extract: P1 (60:16:24), P2 (60:12:28), and P3 (60:8:32). The formulas underwent nutritional value analysis, viscosity testing, and organoleptic evaluations covering color, aroma, texture, and taste. Trained panelists assessed acceptability, and results were presented descriptively and in tabular form. Results showed that all formulas had similar energy content: P1 and P2 at 1.13 kcal/ml, and P3 at 1.12 kcal/ml. Viscosity tests confirmed P2 and P3 met optimal standards for enteral formulas. Organoleptic tests revealed P2 had the most preferred sensory attributes, including a fragrant aroma, smooth texture, and balanced taste. Acceptance tests also favored P2 for its superior sensory properties. In conclusion, P2 (60:12:28) was the most favorable formula, offering optimal nutritional value, viscosity, and sensory appeal. This formula demonstrates potential as a dietary intervention for diabetic patients with hypoalbuminemia, integrating local functional ingredients to support health and recovery.